Isolated bilateral zygomatic complex and zygomatic arch fractures with oral submucous fibrosis: An unusual and rare case report - Alagappan Meyyappan; S Vijayparthiban; M Semmia (Wolters Kluwer Medknow Publications, 2014)
Zygomatic bone forms major buttress of the facial skeleton and plays an important role in facial contour. Fractures of zygomatic complex are second most common only next to nasal bone fractures. Motor vehicle accidents and interpersonal violence are common causes. Bilateral fractures of zygomatic complex and zygomatic arch are very rare. We present a case report of isolated fractures involving bilateral zygomatic complex and zygomatic arch with oral submucous fibrosis, which is unique and first of its kind to be reported.